Comparative Long-Term Durability and Repeatability of Selective versus Argon Laser Trabeculoplasty in Open-Angle Glaucoma: A Systematic Review and Meta-Analysis - Ida Ayu Prama Yanthi; I Made Agus Kusumadjaja; I Gusti Ayu Ratna Suryaningrum; Cokorda Istri Winny Prabasari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Primary open-angle glaucoma (POAG) represents a chronic, progressive optic neuropathy necessitating sustained intraocular pressure (IOP) reduction to prevent irreversible visual field loss. For decades, argon laser trabeculoplasty (ALT) served as the standard laser intervention, yet its utility was circumscribed by thermal coagulative damage to the trabecular meshwork, rendering repeat treatments ineffective. Selective laser trabeculoplasty (SLT), utilizing selective photothermolysis, offers a theoretical advantage in tissue preservation. This study performed a systematic review and meta-analysis to evaluate the comparative long-term durability and repeatability of SLT versus ALT to determine the superior modality for chronic glaucoma management. Methods: A systematic review and meta-analysis were conducted following PRISMA guidelines using data from nine essential manuscripts encompassing randomized controlled trials and comparative cohort studies published between 1999 and 2025. The primary outcome was the standardized mean difference (SMD) in IOP reduction at 12 months and beyond. Secondary outcomes included medication burden reduction and success rates of repeat treatments. Statistical analysis utilized a random-effects model to calculate pooled SMD and 95% confidence intervals (CI). Results: The analysis comprised data from over 800 eyes across diverse demographic cohorts. In the direct comparison of long-term efficacy, SLT demonstrated a non-inferior IOP reduction profile compared to ALT (Pooled SMD: -0.12; 95% CI: -0.28 to 0.05). However, SLT demonstrated statistically superior outcomes in medication reduction, with patients requiring significantly fewer adjuvant hypotensive drops post-laser (SMD: -0.45; 95% CI: -0.68 to -0.22). Repeatability analysis indicated that repeat SLT achieved a 67% success rate in maintaining drop-free status for 18 months, whereas repeat ALT efficacy was negligible due to trabecular scarring. Conclusion: While both modalities effectively lowered IOP initially, SLT demonstrated superior long-term utility driven by significant medication reduction and a favorable safety profile for repeatability. The absence of coagulative damage in SLT supports its positioning as the primary laser intervention, offering a sustainable paradigm that ALT cannot match.